Quality and microbial flora changes of radish paocai during multiple fermentation rounds. (December 2019) - Chen, An-jun; Luo, Wei; Peng, Yi-tao; Niu, Kai-li; Liu, Xing-yan; Shen, Guang-hui; Zhang, Zhi-qing; Wan, Hu; Luo, Qing-ying; Li, Shan-shan
Abstract: Paocai is a popular fermented vegetable side dish or appetizer in China. This study was to investigate the quality and microbial flora changes of paocai during the multiple rounds of fermentation, in order to provide practical suggestions for the industrial production. A total of 4 kinds of lactic acid bacteria were identified based on morphology and calcium dissolution zone size and further 16s RNA identifications. The paocai quality was evaluated on titratable acid, organic acid, amino acid and volatile components content. The results showed that the brine starters after the 4 rounds of fermentation could significantly accelerate the fermentation process from 6 days to only 1–2 days. After 4th round of fermentation, the quality of radish paocai was roughly unified as regard for the microbial flora, organic acid, free amino acid and volatile components content at the maturation point. Therefore, the brine after 4th round of radish paocai fermentation could be used as starters for radish paocai production in industrial scale. Highlights: Starter could accelerate the fermentation process of paocai; After 4 rounds of fermentation could unify the quality of paocai; Starter of brine after 4 rounds decreases fermentation time from 6 days to 2 days; Paocai Quality is significantly influenced by the microbial flora changes.